The Potential Problems of Admissibility and Relevancy of Digital Forensics Evidence in Syariah Courts (International Journal of Psychosocial Rehabilitation, 2020)
Digital forensics evidence has been recognized in Syariah courts by virtue of several related sections under the Syariah Court Evidence (Federal Territories) Act 1997 or other Syariah court evidence enactments. However, due to the lack of challenges on digital evidence cases in Syariah courts, the potential problems or obstacles of digital forensics evidence are unknown among the judges, lawyers, and parties involved. Among the potential problems of admissibility and relevancy of digital forensics evidence are collecting evidence illegally, modifying evidence after it is in possession, and deleting and editing any digital evidence data from the tools. Meanwhile, digital data also changes moment by moment and is invisible to the human eye, and digital technologies are always changing so that the forensic process can seldom be fixed for very long. Therefore, this article aims to examine the potential problems of digital forensics evidence in Syariah courts based on the qualitative approach of literature reviews on the relevant articles, books, statutes, and cases. By having a standard operating procedure (SOP), qualified digital forensics experts and effective digital forensic tools and analysis, they can resolve the problems and subsequently result in the authenticated digital forensics evidence.